Analisis Penerapan Sistem Informasi Akuntansi Terhadap Kinerja Keuangan Umkm Di Era Digital Di Kota Samarinda - Jessika Putriana Iswarno; Dewi Dianata Sapura; L. M. Hasriadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study aims to analyze the influence of financial literacy and the implementation of Accounting Information Systems (AIS) on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the digital era, specifically in Samarinda City. The research employs a qualitative approach with a descriptive design through a literature review method. The data used are secondary data obtained from various scientific sources such as books, journals, and relevant official reports. The data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing.The results indicate that financial literacy plays a crucial role in enhancing the ability of MSME actors to manage business finances, including budgeting, cash flow management, and investment decision-making. Furthermore, the implementation of digital-based Accounting Information Systems improves the quality of financial information produced, particularly in terms of accuracy, timeliness, and relevance. The combination of financial literacy and AIS implementation has been proven to significantly contribute to improving MSMEs’ financial performance, both partially and simultaneously.